The influence of flow experience on mathematical creativity among primary school students in China - Wang, Xueshen; Somasundram, Piriya; Zhang, Jingxian (Frontiers in Education, 2025)
IntroductionMathematical creativity refers to personal ability to propose novel and original solutions or ideas in the process of solving mathematical problems. Many studies have confirmed that flow experiences can affect personal creativity, but few have focused on the influence of flow experiences in mathematics learning on mathematical creativity. This study explores the influence of Chinese primary school students’ flow experience in mathematics class on their mathematical creativity.MethodsThis study adopted a convergent method in mixed research, participants were 273 sixth grade students from a public primary school in central China. For quantitative research, this study collected data by using the Mathematics Flow State Scale and the Mathematical Creativity Scale, and then conducted descriptive statistics, independent sample t-test, and linear regression analysis. For qualitative research, this study selected six students to solve two open-ended mathematical problems and conducted a comparative analysis for their performance.Results and discussionThe results of quantitative research showed that flow experience could positively predict mathematical creativity of primary school students. The qualitative research results showed that students with higher levels of flow experience in mathematics class exhibited better creativity in solving open-ended mathematical problems. Finally, the research results were discussed, and suggestions were made on how to effectively utilize flow experience theory in mathematics class to cultivate students’ mathematical creativity.